Réponses

2013-12-08T15:17:22+01:00
A) Factorisation

A = 9x²+42x+49
   = ((3x)² + 2
× 3x × 7 + 7²
   = (3x + 7)²
B = 25 - 20x + 4x²
   = 4x² - 20x + 25
   = ((2x)² - 2
×2x×5 + 5²
   = (2x - 5)²
b) C = A - B

Réduction :

C = (3x + 7)² - (2x - 5)²
   = ((3x)² + 2 × 3x × 7 + 7²) - ((2x)² - 2 × 2x × 5 + 5²)
   = 9x² + 42x + 49 - (4x² - 20x + 25)
   = 9x² + 42x + 49 - 4x² + 20x - 25
   = 5x² + 62x + 24

Factorisation :

C = (3x + 7)² - (2x - 5)²
   = [(3x+7) - (2x-5)][(3x+7) + (2x-5)]
   = [3x + 7 - 2x + 5] [3x + 7 + 2x - 5]
   = (x + 12)(5x+2)

Pour calculer C lorsque x = 0 tu peux utiliser la forme factorisée :

C = (x + 12)(5x + 2)
   = (0 + 12) (5×0 + 2)
   = 12×2
   = 24

Si x = -1
C = (-1 + 12) (5×(-1) + 2)
   = 11 × (-3)
   = -33

Si x = -0,5

C = (-0.5 + 12) (5×(-0.5) +2 )
   = 11.5 × (-2.5 + 2)
   = 11.5 × (-0.5)
   = - 5.75